The mystery of the missing lion : a Precious Ramotswe mystery for young readers - McCall Smith, Alexander, 1948- (Anchor Books, a division of Random House LLC, 2014)
Staying with Aunty Bee at a safari camp in the Botswana countryside where a film crew is making a movie about a lion, nine-year-old Precious Ramotswe and her resourceful new friend Khumo use their detective skills to find the movie star lion when he goes missing.